(3fRgg GdYGed aj GdYed HGdQHY GdcGeds - (3eMeO Hf eMeO Hf eMeO GHf HgGOQ, CHh GdaVd, ceGd GdOjf GdeDefj,J (B877 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3gPg QSGdg dNUJ ajgG eMGSf GdQSGFd hNUUJgG HeG jJYdb HGdQHY GdcGed ef GdeSGFd s
(3BNQgG (B:s
(3aEf SGhi GdHGbi MUf GdaLQ JhSW Chd hbJ GdaLQ hcPG jYad HeWGdY WdhYg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B40 - (3U(B45s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B297s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B105 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B1050) s
Keywords: (3Gdadcs